Impact of Unemployment on the Global Economy: Causes and Consequences - Ramos Bravo, Maria Ibelia (2023)
Unemployment is a macroeconomic challenge in developing countries, along with inflation and real GDP. There is a clear connection between unemployment and mental health, as unemployed workers experience poorer health compared to those who are employed. To determine the causes and effects, a systematic review of scientific literature was conducted based on the PRISMA statement, using information recorded between 2018 and 2023. The results from 30 selected documents indicate that unemployment has multiple causes, such as changes in economic and technological structure; its consequences include reduced economic growth as the most significant impact. The impact of unemployment on the economy, according to our study, depends on various factors in different regions and contexts.